2006
DOI: 10.1680/adcr.2006.18.4.145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of additives on the properties of α-hemihydrate

Abstract: The effects of Na-succinate and succinic acid on the properties of the α-hemihydrate synthesised from the fluegas desulphurised (FGD) gypsum of the Mae Moh power plant, northern Thailand, by the classical vapour process, were studied in comparison with natural gypsum. It was found that the additives strongly affected the content and microstructure of the α-hemihydrate, and consequently the properties of its dihydrate. The physical and mechanical properties of the hydrated plaster were investigated in conformit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Mix the gypsum and salt solution, and add in some deionized water to prepare the aqueous salt solution with gypsum. [5] Put the sample solution into reflux device, and heat at different temperature for 2h. [6,7] After heating, filter the solution immediately.…”
Section: Methodsmentioning
confidence: 99%
“…Mix the gypsum and salt solution, and add in some deionized water to prepare the aqueous salt solution with gypsum. [5] Put the sample solution into reflux device, and heat at different temperature for 2h. [6,7] After heating, filter the solution immediately.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, gypsum pastes have their pumpability impaired as thickening times are less than 20 minutes. For applications that require longer pumping times, retardant additives must be added to gypsum paste systems, and thickening time tests must be carried out (Panpa & Jinawath, 2006).…”
Section: Eq (1)mentioning
confidence: 99%
“…During this process, the formation of HH crystal is related to temperature, salt solution, time, and the crystal modifier (e.g., inorganic acids). [14][15][16] Li and Demopoulos [17,18] developed a chemical model for the solution process of DH, HH, AH, and constructed the phase-transition diagrams in the CaSO 4 -HCl-CaCl 2 -H 2 O system in which the region for forming a-HH was presented. Guan et al investigated the phase-transition behaviors of a-HH and DH in KCl solutions and found that the metastability of a-HH heavily relied on KCl concentration and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…During this process, the formation of HH crystal is related to temperature, salt solution, time, and the crystal modifier (e.g., inorganic acids). [ 14‐16 ] Li and Demopoulos [ 17,18 ] developed a chemical model for the solution process of DH, HH, AH, and constructed the phase‐transition diagrams in the CaSO 4 –HCl–CaCl 2 –H 2 O system in which the region for forming a‐HH was presented. Guan et al.…”
Section: Introductionmentioning
confidence: 99%